Asthma-related deaths. Issue 1 (December 2016) - D'Amato, Gennaro; Vitale, Carolina; Molino, Antonio; Stanziola, Anna; Sanduzzi, Alessandro; Vatrella, Alessandro; Mormile, Mauro; Lanza, Maurizia; Calabrese, Giovanna; Antonicelli, Leonardo; D'Amato, Maria
Abstract Despite major advances in the treatment of asthma and the development of several asthma guidelines, people still die of asthma currently. According to WHO estimates, approximately 250, 000 people die prematurely each year from asthma. Trends of asthma mortality rates vary very widely across countries, age and ethnic groups. Several risk factors have been associated with asthma mortality, including a history of near-fatal asthma requiring intubation and mechanical ventilation, hospitalization or emergency care visit for asthma in the past year, currently using or having recently stopped using oral corticosteroids (a marker of event severity), not currently using inhaled corticosteroids, a history of psychiatric disease or psychosocial problems, poor adherence with asthma medications and/or poor adherence with (or lack of) a written asthma action plan, food allergy in a patient with asthma. Preventable factors have been identified in the majority of asthma deaths. Inadequate education of patients on recognising risk and the appropriate action needed when asthma control is poor, deficiencies in the accuracy and timing of asthma diagnosis, inadequate classification of severity and treatment, seem to play a part in the majority of asthma deaths. Improvements in management, epitomized by the use of guided self-management systems of care may be the key goals in reducing asthma mortality worldwide